Long-Term Computed Tomographic Evaluation of Alveolar Bone Formation in Patients with Unilateral Cleft Lip and Palate after Early Secondary Gingivoalveoloplasty. Issue 2 (February 2016) - Meazzini, Maria Costanza; Corno, Martina; Novelli, Giorgio; Autelitano, Luca; Tortora, Chiara; Elsido, Davide; Garattini, Giovanna; Brusati, Roberto
Abstract : Background: The goal of this study was to evaluate with a three-dimensional method the long-term quality of alveolar ossification in unilateral cleft lip and palate patients who underwent early secondary gingivoalveoloplasty according to the Milan surgical protocol. Methods: The sample consisted of 63 computed tomographic scans of unilateral cleft lip and palate patients in permanent dentition. The average age at the time of assessment was 15.7 years. Alveolar thickness, nasoalveolar height, nasal floor ossification, and hard palate morphology were evaluated using dental, axial, and coronal cuts on computed tomographic scans and three-dimensional models. All measurements were normalized and ratios of the affected side versus the nonaffected side were provided. Volume measurements and ratios of each hemimaxilla were added. The presence or absence of the permanent lateral incisor on the cleft side was also recorded. Results: Alveolar thickness and height were ideal or good, respectively, in 89.5 and 91.4 percent of the sample. Insufficient ossification (<25 percent) was found in three patients (5.2 percent), and only one of them (1.7 percent) presented no bone bridging. A statistically significant association was detected between the degree of alveolar ossification, the type of nasal floor ossification, and volume ratio. Conclusions: Early secondary gingivoalveoloplasty seemed to allow an adequate ossification of both the alveolar and nasal region. Three-dimensional evaluation of the alveolar cleft ossification provided further information on alveolar bridging and allowed evaluation of the bone availability for implant placement. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.